Proceedings of the 1st International Conference on Social and Political Development (ICOSOP 2016) 2017
DOI: 10.2991/icosop-16.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Career Maturity Among High School Students in Medan

Abstract: Abstract-This purpose of this research was to know about career maturity of high school students. Career maturity needs to be examined considering many students not ready to choose a career direction when later graduated high school. As for this research involve 206 students from several schools in Medan City. We used the Career Maturity Inventory form C by Crites & Savickas [8] who were adapted into Indonesian language. CMI Form C provides a total score for career choice readiness, and consist of four dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Song, Bong, Lee, & Kim [3] mengemukakan bahwa kematangan karir merupakan tingkat kesiapan individu dalam mengatasi permasalahan yang berkaitan dengan pilihan dan pengambilan keputusan karir, maka dari itu sejalan dengan yang dikemukakan oleh Eliana, et. al [4] bahwa kematangan karir seharusnya menjadi suatu hal yang dianggap penting karena individu akan dapat membuat keputusan karir yang sesuai dengan minat dan bakatnya sehingga kelak ketika menghadapi pekerjaan dalam dunia karir, serta individu akan memiliki performa yang optimal.…”
Section: Aunclassified
“…Song, Bong, Lee, & Kim [3] mengemukakan bahwa kematangan karir merupakan tingkat kesiapan individu dalam mengatasi permasalahan yang berkaitan dengan pilihan dan pengambilan keputusan karir, maka dari itu sejalan dengan yang dikemukakan oleh Eliana, et. al [4] bahwa kematangan karir seharusnya menjadi suatu hal yang dianggap penting karena individu akan dapat membuat keputusan karir yang sesuai dengan minat dan bakatnya sehingga kelak ketika menghadapi pekerjaan dalam dunia karir, serta individu akan memiliki performa yang optimal.…”
Section: Aunclassified
“…Terdapat beberapa faktor lain yang mempengaruhi tinggi-rendahnya kematangan vokasional individu sebagaimana disampaikan oleh Eliana et al (2016), seperti:…”
Section: Diskusiunclassified
“…Major selection and career exploration in late adolescence will bring them to a decision-making process (Purwanta, 2012). The results of a research on 206 high school students in Medan City using Career Maturity Inventory, which was translated into Indonesian, indicated that high school students are still looking for more information about their careers and also not confi dent in their abilities (Eliana, Supriyantini, & Tuapattinaja, 2016).…”
Section: Introductionmentioning
confidence: 99%